Degradasi Warna dan COD pada Pengolahan Air Lindi TPA Bakung dengan Metode Fenton - Teguh, Dedi; Cendekia, Devy; Sari, Nita Pita; Putri, Cynthia Eka (Jurnal Sains dan Teknologi Lingkungan, 2024)
The main problem in the Bakung final processing place is the infiltration of leachate with high concentrations of organic and inorganic substances. Leachate from landfills is usually characterized by a foul odor, a black color, high COD values, and toxicity. This is very dangerous if it is directly flown into the ground or water body because it can pollute the environment. Therefore, it is necessary to carry out effective leachate treatment. One way to treat leachate is using Fenton method, which is a development of  advanced oxidation processes technology. The objectives of this research are to treat leachate using the Fenton method and determine the effect of the Fenton molar ratio (1:150, 1:200, 1:250) and reaction time (30, 60, 90, 120 minutes) on color and COD degradation. Optimum conditions were achieved at a Fenton molar ratio of 1:150 and a reaction time of 120 minutes, with maximum color and COD degradation percentages of 91.4% and 92.4%, respectively. The results of this research show that the Fenton method is very effective on color and COD degradation in leachate and has met the leachate water quality standards for businesses and/or final waste processing activities.